Effect of ablation at high‐dominant frequency sites overlapping with low‐voltage areas after pulmonary vein isolation of nonparoxysmal atrial fibrillation. (6th August 2019) - Kumagai, Koji; Minami, Kentaro; Sugai, Yoshinao; Sumiyoshi, Takenori; Komaru, Tatsuya
Abstract: Background: The relationship between high‐dominant frequency (DF) sites and low‐voltage areas (LVAs) in nonparoxysmal atrial fibrillation (AF) patients still remains unknown. Objective: This study aimed to evaluate the effect of ablation at high‐DF sites overlapping with LVAs after pulmonary vein ablation (PVI) of nonparoxysmal AF. Methods: A total of 128 consecutive nonparoxysmal patients with atrial fibrillation (53 persistent AF) were retrospectively investigated. The patients with AF were divided into two groups: patients with circumferential PVI alone (PVI group, n = 57) and those with PVI followed by a DF‐based ablation (DF group, n = 71). Results: The patient characteristics did not significantly differ between the two groups. However, the LVA ( < 0.5 mV)/left atrial (LA) surface was significantly greater in the DF than the PVI group (22% vs 16%, P = .02). The total max‐DF sites overlapping with LVAs in the LA were significantly greater in the DF than the PVI group (91% vs 10%, P = .001). The atrial arrhythmia freedom on antiarrhythmic drugs in the DF group was significantly greater than that in the PVI group during 10.0 ± 3.2 months of follow‐up (83.1% vs 64.9%, log‐rank test P = .021). The event‐free survival in the PVI group decreased according to the LVA extent while it was > 80% in the DF group. The event‐free survival in patients with AF especially with extensive LVAs ( ≥ 30%) in the DF group was significantly greater than that in the PVI group (81.0% vs 45.5%, log‐rank test P = .035). Conclusions: High‐DF sites overlapping with LVAs after the PVI may be potential selective targets for modification of atrial substrates in nonparoxysmal AF patients.